A comparative investigation of dibenzo[a, c]phenazine and quinoxaline donor–acceptor conjugated polymers: Correlation of planar structure and intramolecular charge transfer properties. (17th December 2019) - Kim, Doo Hun; Han, Yong Woon; Moon, Doo Kyung
Abstract: An indacenodithienothiophene (IDTT) donor was copolymerized with phenazine (Phz) and quinoxaline (Qx) derivatives, which roled as acceptor units, to obtain novel donor–acceptor conjugated polymers PIDTT-Phz and PIDTT-Qx, respectively. The electrostatic potential surfaces(ESP) of these polymers were calculated using density functional theory according to the shape of the phenyl structure. Intramolecular charge transfer effects were much stronger in PIDTT-Phz than in PIDTT-Qx owing to the phenanthrene moiety in the former. X-ray diffraction measurements showed that the polymers exhibited ordered lamellar structures with conventional face-on π-stacking. The PIDTT-Phz device with a 1:2 polymer/PC71 BM ratio showed a power conversion efficiency (PCE) of 6.7%, which is among the highest PCEs achieved by Phz derivative-based donor polymers reported to date. The PCE of the PIDTT-Qx device with a 1:3 polymer/PC71 BM ratio was 7.2%. Graphical abstract: We designed donor–acceptor conjugated polymers, PIDTT-Phz and PIDTT-Qx, with high solubility were synthesized by introducing Qx derivatives with alkoxy chain at the para-position as an acceptor and IDTT as donor. Especially, designated two polymers exhibited improved PCE as well as higher V OC and J SC compared to the reference materials. This work would suggest relational designation for the donor in donor:acceptor system. Image 1 Highlights: We designed donor–acceptor conjugated polymers, PIDTT-Phz and PIDTT-Qx. We have focused on the study of the correlation between planar structure and intramolecular charge transfer properties. PIDTT-Phz have showed that fused phenanthrene rings can make the molecular backbone more rigid and coplanar, thereby enhancing effective π-conjugation. PIDTT-Qx showed PCE of 7.2% with high photo-current (15.1 mA/cm 2 ).